(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Transport is one of the essential components of tourism activities. The relationship between transport and tourism development is very important because it contributes significantly in the development of tourism. It overcomes the physical social and economic development of human beings. It overcomes the physical constraints of distance and meets the human needs for movement over the space. It provides a link between the origin and destination of tourism. The movement of human beings at national and international level is taking place because of various means of transport